Utilizing Telemedicine to Improve Access to Healthcare Services in Remote Areas - Efendi, Mona; Sulistiani , Retno (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the use of telemedicine in improving access and quality of health services in remote areas and identify the factors that influence it. The method used is a quantitative approach with descriptive and inferential analysis, including correlation, regression, and paired sample t-test. The main results show that 63.3% of respondents have used telemedicine in the last three months, with a higher level of use among health workers (76.7%) than the public (58.3%). The implementation of telemedicine has been shown to significantly increase access to health services, indicated by an increase in the score from 2.3 to 3.6 (a 56.5% increase) with a significance value (p = 0.001 < 0.05). The most influential factor is perceived usefulness with an average value of 4.1 and a strong correlation (r = 0.68), followed by access to technology with a regression coefficient of 0.42. In addition, service quality has also improved, reflected in an increase in patient satisfaction from 3.1 to 4.0. These findings indicate that telemedicine is effective in improving access to and quality of healthcare services, although it still faces challenges in terms of digital literacy, technological infrastructure, and user trust.